PENGARUH PERLAKUAN HCl PADA KRISTALINITAS DAN KEMAMPUAN ADSORPSI ZEOLIT ALAM TERHADAP ION Ca2+ - Pardoyo, Pardoyo; Listiana, Listiana; Darmawan, Adi (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT–It has been done a research to determine the influence of hydrochloric acid treatnent to the crystalinity and adsorption capability of natural zeolite to Ca2+ ion. Activation process was conducted by refluxing of zeolite with KMnOa 0.5 M and HCI (1:1) for 4 hours with temperature of 80